2020
DOI: 10.1177/2048872620922784
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac safety of off-label COVID-19 drug therapy: a review and proposed monitoring protocol

Abstract: More than 2,000,000 individuals worldwide have had coronavirus 2019 disease infection , yet there is no effective medical therapy. Multiple off-label and investigational drugs, such as chloroquine and hydroxychloroquine, have gained broad interest due to positive pre-clinical data and are currently used for treatment of COVID-19. However, some of these medications have potential cardiac adverse effects. This is important because up to one-third of patients with COVID-19 have cardiac injury, which can further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
136
0
11

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 31 publications
0
136
0
11
Order By: Relevance
“…1 Hydroxychloroquine and chloroquine have also been associated with conduction disorders, widened QRS duration and T-wave inversion on ECG, myocardial toxic effects, and exacerbation of underlying myocardial dysfunction. 2,3 Therefore, hospitals have been implementing ECG-based monitoring protocols whenever these agents are used for treatment of patients with COVID-19. However, severely ill patients placed in prolonged prone positioning to treat refractory hypoxemia secondary to acute respiratory distress syndrome often will have ECG leads placed on their back side instead, directly posterior to lead placement in the traditional supine position ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…1 Hydroxychloroquine and chloroquine have also been associated with conduction disorders, widened QRS duration and T-wave inversion on ECG, myocardial toxic effects, and exacerbation of underlying myocardial dysfunction. 2,3 Therefore, hospitals have been implementing ECG-based monitoring protocols whenever these agents are used for treatment of patients with COVID-19. However, severely ill patients placed in prolonged prone positioning to treat refractory hypoxemia secondary to acute respiratory distress syndrome often will have ECG leads placed on their back side instead, directly posterior to lead placement in the traditional supine position ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…As of now, favipiravir is not available in the U.S. or European countries, perhaps because the animal experiments showed that the antiviral agent can be associated with teratogenic effects. Favipiravir is contraindicated in women with known or suspected pregnancy [ 75 ]. Favipiravir is also associated with QT prolongation [ 76 ].…”
Section: Viral Polymerase Inhibitorsmentioning
confidence: 99%
“…In this intricate scenario, there is no consensus on optimal management to mitigate the underlying torsadogenic substrate. Different guidelines and authors have proposed recommendations for QT monitoring [104][105][106][107]: although there is general agreement on the need for baseline QT assessment and general discontinuation rules (e.g., QT interval, corrected for cardiac frequency, > 500 ms, and increases > 60 ms), the timing for electrocardiographic re-assessment and re-check may vary depending on the drug (e.g., after 3-4 days of therapy initiation with hydroxychloroquine/azithromycin), as well as underlying expected susceptibility (e.g., in patients with borderline QT and structural heart disease, telemetry should be considered, also with wearable devices for out-of-hospital monitoring). Notwithstanding practicalities in carrying out home monitoring, timely correction of electrolyte imbalances before prescribing QT-prolonging agents (and monitoring relevant blood levels) is recommended, although it is unclear whether an empirical approach through preventive administration of potassium and magnesium is actually effective in mitigating the risk of TdP occurrence.…”
Section: Torsadogenic Liability In Cardio-oncology: Focus On Patientsmentioning
confidence: 99%